The dynamic characteristics of the shearer cable drag system. - Bo Xie; Feida Wang; Jing Liu; Zhanjun Xu; Shuaishuai Gao; Lijuan Zhao (PLoS ONE)
Based on the 5615 working face of Beisu Coal Mine, a virtual prototype of the shearer cable drag system was developed using the MG2×70/325-BWD electric traction shearer as the carrier, in combination with CERO and ADAMS software. The shearer cable was equivalently modeled using the discrete rigid body method to study the dynamic characteristics of the drag system. This research provides a foundation for the design and optimization of both the cable and cable clamps. The results indicate that during the bending process of ordinary and reinforced cables in the cable drag system, the tensile force between the cable clamps increases from approximately 28 N and 37 N to a maximum value of 133 N and 146 N, respectively, before decreasing to around 57 N and 66 N. At the connection point between the drag system and the shearer, the tensile force between the cable clamps fluctuates and increases, reaching a maximum value of 925.2 N and 1134.7 N when the shearer reaches the end of the working face. These values are significantly lower than the cable clamp's breaking tensile strength of 70 kN, with peak values of 57.4 N and 94.1 N, respectively. During the cable bending process, The contact force with the cable clamp continuously changes with the bending angle, During 0 ~90°, the contact force between ordinary and reinforced cable and cable clamp gradually increases to the maximum values 61.3N and 86.2N, After 90 have plummeted to near 23 N and 25 N, In the process of dragging the cable to the top of the roller, it fluctuates between 45.2~51.7 N and 66.3~73.6 N respectively, Cable exit bends are slowly reduced to fluctuations around 16 N and 17 N, The tensile force between ordinary and reinforced discrete cables increased to around 58.4 N and 80.5 N and then decreased to around 12.6 N and 32.8 N, respectively. During the bending process of reinforced cables, the average contact force with the cable clamps increased by 22.3 N compared to the ordinary cables, while the average discrete tensile force between the cables increased by 18.7 N. Although the tensile and contact forces of the reinforced cable are slightly higher than those of the ordinary cable, the reinforced cable has a higher safety factor and greater adaptability. The drag motion of the cable is correlated with the characteristics of the ring-chain drive, and the drag speed and tensile force exhibit periodic variations due to the polygonal effect of the chain drive. The findings provide valuable insights for intelligent cable drag research and lay the foundation for the optimization of mining cables and cable clamps.